Reflexões sobre o ensino da álgebra para professores de matemática do ensino fundamental da rede municipal de manaus: uma proposta metodológica - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
This work will present clearly and succinctly about reflections on the teaching of algebra for mathematic teachers elementary school from 6o to 9o year of Municipal Education System of Manaus: a methodological proposal, emphasizing on the importance of continuing education, practicing and reflections of mathematics educators and to demonstrate how we can help in algebra learning: generalization, exploration, formulation, validation of conjectures about the arithmetic properties and those who want to master mathematical formulas. Further, it aims to support in math workshops, simulating everyday situations making mathematics most pleasurable and closer to your world, thus bringing the reality of mathematics for students.
Keywords: Professores - Formação continuada; Ensino da álgebra - Ensino Fundamental; Teachers - Continuing Education; Algebra Education - Elementary Education; CIÊNCIAS EXATAS E DA TERRA: MATEMÁTICA